Implementasi Virtual Library Berbasis Open Source Model Offline Di Mts Darul Hikmah Ngompak Kecamatan Ngrambe Kabupaten Ngawi - Amirulliani, Nindya; Triyono, Ramadhian Agus (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2013)
Abstract : ICT (Information and Communication Technology) becomes vital thing in this modern era, especially in education. Because of this development, library based technology (computerization) is needed for increasing the quality and the speed of service for the library users so that it can help the process of learning and teaching in the school. It functions to be the resource for teachers and the students in implementing technology especially in the village schools which have difficulty in internet access, like MTs Darul Hikmah Ngompak. For this case, Virtual library based offline-open source is an alternative because of its usefulness in the teaching learning process. It can be references and source of lesson materials in e-book form such encyclopedia, search wiki, simulation through the learning video and flash that can be accessed using Localhost connection. Based on the observation, the result of implementation Virtual Library in MTs Darul Hikmah shows that Virtual Library is very helpful for teachers and the students. Some teachers are interested in managing, serving and directing the class using the media and the students become more enthusiasm in listening to, understanding and learning lesson using Virtual Library which also provides the exciting game and animation. However, the range of usefulness of the collection depends on how to organize and make it useful. Keywords : Virtual Library, Student, Teacher, Technology Abstrak : Teknologi informasi dan komunikasi atau ICT (Information and Communication Technology) telah menjadi bagian yang tidak terpisahkan dari kehidupan manusia modern terutama dalam bidang pendidikan. Menyikapi perkembangan ICT, Perpustakaan berbasis teknologi (komputerisasi) sangat dibutuhkan untuk meningkatkan kualitas dan kecepatan proses layanan pada pengguna perpustakaan sehingga dapat memperlancar proses belajar mengajar di lingkungan madrasah. Untuk menyetarakan resouce serta ketrampilan guru dan siswa didik dalam penerapan teknologi pada sekolah-sekolah tingkat desa yang tidak tersedia atau minim fasilitas internet seperti MTs Darul Hikmah Ngompak. Virtual Library berbasis open source model offline adalah alternatif atau solusi kendala ini. Selain itu, juga berperan sebagai penyedia informasi bahan ajar berupa ebook sebagai referensi, ensiklopedia wiki model search, simulasi melalui video pembelajaran maupun flash yang akan memperkaya khasanah keilmuan guru dan siswa yang dapat diakses dengan jaringan teknologi Localhost. Hasil pengamatan dari penerapan Virtual Library di MTs Darul Hikmah Ngompak, menunjukkan bahwa guru sangat berminat mempelajari, mengoperasikan dan mempraktekkan dalam kelas. Sedangkan siswa lebih antusias belajar dengan menggunakan Virtual Library yang juga menyediakan game dan animasi yang menyenangkan. Namun bagaimana koleksi digital dimanfaatkan, sangat tergantung pada bagaimana fasilitas tersebut dibuat dan diorganisasikan, serta disajikan. Kata Kunci : Virtual Library, Guru, Siswa, Teknologi